2016
DOI: 10.1590/1983-40632016v4639610
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of nutrients and agronomic performance of grafted seedless watermelon

Abstract: Chemical fertilizing is one of the main inputs that increase watermelon production costs. Watermelon grafting with compatible rootstocks and a vigorous root system may increase the efficiency of nutrients absorption. This study aimed at determining the accumulation of dry matter and nutrients, as well as the agronomic performance of grafted watermelon. The triploid 'Precious Petite' watermelon was used as graft and the Line BGCIA941 (Citrullus lanatus var. citroides) as rootstock. The experimental design consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 15 publications
(19 reference statements)
2
7
2
Order By: Relevance
“…The maximum accumulation of S by the fruit was 1.06 g plant -1 , and was characterized by being slow in the first 44 DAS and then increasing in demand until the end of the cycle. The results found agree with those obtained by Grangeiro & Cecílio Filho (2005a), for the Nova hybrid, and Santos et al (2016), for crop BGCIA 941, which reported accumulated sulfur values of 1.75 and 1.70 g plant -1 , respectively. In terms of micronutrient accumulation, manganese was the most accumulated in Top Gun, reaching 404.1 mg plant -1 at 71 DAS (Figure 8).…”
Section: Progression Of Nutrient Accumulationsupporting
confidence: 91%
See 4 more Smart Citations
“…The maximum accumulation of S by the fruit was 1.06 g plant -1 , and was characterized by being slow in the first 44 DAS and then increasing in demand until the end of the cycle. The results found agree with those obtained by Grangeiro & Cecílio Filho (2005a), for the Nova hybrid, and Santos et al (2016), for crop BGCIA 941, which reported accumulated sulfur values of 1.75 and 1.70 g plant -1 , respectively. In terms of micronutrient accumulation, manganese was the most accumulated in Top Gun, reaching 404.1 mg plant -1 at 71 DAS (Figure 8).…”
Section: Progression Of Nutrient Accumulationsupporting
confidence: 91%
“…According to Marschner (2011), of the total accumulated magnesium in the plant, between 6 and 25% is related to the chlorophyll molecule and, therefore, the macronutrient is expected to accumulate in greater proportion in the leaves . However, the results suggest that there are differences between the cultivars in terms of absorption and redistribution of magnesium, a hypothesis that has already been verified in standards of grafted watermelon (Santos et al, 2016).…”
Section: Progression Of Nutrient Accumulationsupporting
confidence: 57%
See 3 more Smart Citations